Co-biodrying of sewage sludge and organic fraction of municipal solid waste: A thermogravimetric assessment of the blends. (15th July 2019) - Zhang, Difang; Luo, Wenhai; Liu, Yifei; Yuan, Jing; Li, Guoxue
Highlights: Co-combustion properties of sewage sludge and OFMSW during biodrying was assessed. There existed interaction at high temperature during co-combustion process. Co-biodrying for 9 days enhanced the ignition performance and burnout efficiency. Equivalent amount of sludge and OFMSW showed higher S value during biodrying. Biodrying process with 9–12 days is preferable. Abstract: This study investigated the thermogravimetric properties of sewage sludge and organic fraction of municipal solid waste (OFMSW) during their co-biodrying at different fractions. Sewage sludge and OFMSW were co-biodried at the mass proportion of 0%, 42.5% and 85% (of the total wet weight), respectively, with 15% cornstalk as the bulking agent. Results show that of these three raw materials, OFMSW exhibited the lowest ignition temperature and the highest burnout temperature. Moreover, OFMSW had a better comprehensive combustion performance ( S ) than sewage sludge. Blending OFMSW, sewage sludge and cornstalk showed the highest S value (4.0 × 10 −7 % 2  min −2  °C −3 ). In addition, there existed certain interactions between the co-combustion process, especially at high temperature stage. The burning characteristics, including ignition performance, burnout efficiency, DTGmax and S increased with fluctuations in the first 6–9 days of co-biodrying process, and then declined in all treatments. Hence, 15-day of biodrying made the product with poor burning behavior ( S value of 1.0 × 10 −7 –1.4 × 10 −7 % 2  min −2  °C −3 ). More importantly, the optimal combustion performance was observed when co-biodrying the same amount (42.5%) of sewage sludge and OFMSW with the peak of 8.3 × 10 −7 % 2  min −2  °C −3 achieved on day 9. In addition, the blends were easier to burn after the biodrying process.